Patients' privacy: a literature review - Mehrdad N; Parsa Yekta Z; Jolaee S (Tehran University of Medical Sciences, 2004)
The concept of privacy, which is used in many disciplines, is a basic human need and also is recognized as an important concept in nursing. The concept of privacy has been described in various dimensions including physical, psychological, social and informational privacy. In this article we review these dimensions. Most of the studies related to the privacy have been carried out in the area of physical privacy. One of the basic areas of privacy in hospitals is related to data protection and the prevention of information inaccuracies. Major factors that threaten the privacy include intrusion upon the seclusion or physical boundaries and unnecessary physical touch. In order to decrease these problems, health worker need to find a new approach of working with patients. Review of the literature showed that only a few studies about the privacy of patients have been carried out. To encourage research in this field, accurate instruments should be developed in order to measure different aspects of the privacy, an aim that is difficult to achieve because of the complex nature of the concept. It is also important that necessity of observing patients' privacy systematically be thought to medical students